IDENTIFIKASI FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH PENGGUNA INTERNET BANKING PADA BANK NAGARI CABANG SYARIAH BUKITTINGGI - Sawitri Sawitri; Rini Elvira (Adisam Publisher, 2025)
The development of information technology has brought significant changes to the banking industry, including the application of internet banking. This research aims to identify factors that influence customer satisfaction with internet banking users at Bank Nagari Syariah Branch, Bukittinggi. Based on initial observations, seven factors were found that influence customer satisfaction, namely: product quality, service quality, fulfillment of emotional aspects, product price, costs, ease of access, and transaction experience. This research uses a quantitative approach with a survey method involving 30 customers who use internet banking. Data was collected through questionnaires and analyzed using descriptive statistics. The research results show that the factors of service quality, fulfillment of emotional aspects, and product price have a high level of satisfaction among customers. Meanwhile, product quality, cost, ease of access and transaction experience factors show lower levels of satisfaction. It is hoped that these findings will provide insight for Bank Nagari Syariah in improving internet banking services and providing better satisfaction for customers. Apart from that, this research also contributes to the literature regarding customer satisfaction and the use of sharia banking technology in Indonesia.